الدلائل الصدوية لاضطربات الأذينة اليسرى عند المرضى الشباب المصابين برجفان أذيني انتيابي معزول - رضوان عبد الناصر; بله حسام; شاكر أحمد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة (12) مريضاً لديه رجفان أذيني انتيابي معزول، و (12) شخصاً طبيعياً لفئات عمرية متقاربة ( سنة)، وتم قياس أبعاد الأذينة اليسرى في الاتجاه: (أمامي – خلفي) عبر النافذة جانب القصية وبمنظر المحور الطويل، وفي الاتجاه (سفلي – علوي) والاتجاه (أنسي – وحشي) ومساحة الأذينة اليسرى عبر النافذة القمية وبمنظر رباعي الحجرات. فوجد أن هناك اختلاف واضح في بعض هذه الأبعاد بين الأشخاص المصابين بالرجفان الأذيني الانتيابي المعزول والأشخاص الأسوياء مما يدل على أنَّ المرضى مع رجفان أذيني انتيابي معزول قد يكون لديهم اضطرابات بنيوية صغيرة في الأذينة اليسرى. The study included (12) patients with lone paroxymal atrial fibrillation, and (12) normal persons of the same age ( years old) and measurements of the left atrium (anteroposterior) dimension by the parasternal long – axis view, and (inferosuperior) and (mediolateral) dimensions and area of the left atrium were taken by the apical 4 – chamber view. It was found that there is a clear difference in some of these measurements between normal persons and patients with these personal AF. This may reveal that patients with a lone paroxysmal atrial fibrillation might have small structural abnormalities in the left atrium.